Aberrant glycosylation patterns as potential biomarkers for diagnosis and disease progression in bullous pemphigoid - Haijun Miao; Jundan Yang; Yaxing Bai; Shengxian Shen; Xia Li; Lixin Yue; Gang Wang; Erle Dang (Frontiers in Immunology)
ObjectivesBullous pemphigoid (BP) is a prototypical autoimmune disease characterized by the production of autoantibodies against hemidesmosomal proteins BP180 and BP230. Aberrant glycosylation has emerged as a possible mechanism linked to the pathogenesis and progression of autoimmune diseases. However, the precise alterations in glycosylation in BP remain largely unknown. In this study, we explored the molecular mechanisms of abnormal glycosylation in BP pathogenesis.MethodsWe systematically investigated the glycosylation changes in serum, blister fluid, and saliva from BP patients using lectin microarray assays and lectin-based enzyme-linked immunosorbent assays.ResultsOur findings revealed increased glycosylation modifications of sialic acid, galactose, and fucose in serum proteins from BP patients, as well as enhanced fucosylation, galactosylation, and biantennary N-glycan glycosylation in blister fluid proteins. Notably, these abnormal modifications of monosaccharides correlated with the clinical indicators of BP. Furthermore, we observed that glycosylation patterns in saliva were associated with disease severity, suggesting their potential as valuable non-invasive diagnostic markers for BP.ConclusionThese discoveries indicate that aberrant glycosylation patterns may provide insights into the pathogenesis of BP and serve as potential biomarkers for diagnosing and monitoring the disease.